Implementasi Pembinaan Dalam Meningkatkan Spiritualitas Warga Binaan Pemasyarakatan di Lapas Narkotika Kelas IIB Banyuasin - M. Anugrah Bimantara; Denny Nazaria Rifani (Universitas Pahlawan Tuanku Tambusai, 2022)
Correctional institutions are one of the places for fostering people who are ensnared by the law. It is hoped that the implementation of the coaching will enable the inmates to be able and able to recognize themselves, avoiding the inmates from repeating their actions. The purpose of this study was to determine the implementation of coaching in improving the spirituality of the inmates in the prison of Narcotics Class IIB Banyuasin. This study uses a qualitative method located in the Narcotics Prison Class IIB Banyuasin. Sources of data obtained from direct object observation and supported by interviews. The data analysis technique uses data collection, data reduction, data presentation, and drawing conclusions. The results obtained from this study indicate that the implementation of guidance in the Class IIB Banyuasin Prison has been carried out well and positively with the help of third party collaboration from the Banyuasin Ministry of Religion, the Zakat charity Foundation (Yazri) PT Pusri, the Benevolent Foundation of the city of Palembang, and the An-nur Islamic Boarding School. This cooperation resulted in several programs that have been implemented well. The obstacles that occur in the implementation of spiritual development are related to the coaching officers owned by Lapass which still amount to 1 (one) person, the lack of a budget that meets the activities, the methods given to inmates who are still monotonous, and the lack of motivation of inmates to take part in spiritual development activities.